DEGRADATION OF PETROLEUM REFINERY WASTE BY A CONSORTIUM OF HYDROCARBONOCLASTIC BACTERIA ON SEVERAL C:N:P RATIO - Syukria I Zam; irfan mustafa (Journal of Tropical Life Science, 2012)
Bioremediation is an alternative method to treat petroleum waste using microorganism into nontoxic end product. The method is relatively cheap, effective, and environmental friendly. A key factor influencing bioremediation process for petroleum refinery waste treatment is C:N:P ratio of bacterial growth medium. The objective of this research was to obtain C:N:P ratio of Stone Mineral Salt Solution (SMSS) medium that allow optimal degradation of petroleum refinery waste by consortium of hydrocarbonoclastic bacteria. C:N:P ratio of SMSS medium was adjusted to ratio of 100:10:1, 100:10:0.5, 100:5:1, and 100:5:0.5. We demonstrate that optimal degradation of petroleum refinery waste by a consortium of hydrocarbonoclastic bacteria was achieved in SMSS medium with C:N:P ratio of 100:5:1. It allowed 66.55% degradation of total petroleum hydrocarbon (TPH) and 85.18 % decrease of chemical oxygen demand (COD) value.